A multicenter, randomized, double‐blind comparison of two hyaluronic acid fillers in mid‐face volume restoration in Asians: A 2‐year extension study. Issue 2 (9th February 2021) - Jung, Joon Min; Lee, Woo Shun; Yoon, Jihae; Paik, Seung Hwan; Han, Hye Sung; Lee, Woo Jin; Chang, Sung Eun; Won, Chong Hyun; Kim, Beom Joon
Abstract: The long‐term effectiveness and safety of hyaluronic acid fillers in mid‐face volume restoration in Asians remain unclear. The objective of this study was to compare the long‐term effectiveness and safety of Neuramis Volume Lidocaine (SHAPE‐NVL) and Juvederm Voluma with Lidocaine (VYC‐20L) in mid‐face volume restoration in Asians. Overall, 88 Korean subjects with moderate‐to‐severe age‐related mid‐face volume deficit on the Mid‐Face Volume Deficit Scale (MFVDS) received SHAPE‐NVL on one side and VYC‐20L on the contralateral side of the face. Of the 81 subjects who completed the 48‐week primary study, 69 subjects were enrolled in an extension study lasting 104  weeks. MFVDS score and global aesthetic improvement were assessed at each visit. Response was defined as a ≥1‐point reduction in MFVDS. At weeks 36 and 48, the responder rates for SHAPE‐NVL were 81.93% and 80.72%, while those for VYC‐20L were 85.54% and 81.92%, respectively. At the 104‐week visit, the responder rates were 73.91% and 72.46% for SHAPE‐NVL and VYC‐20L, respectively. No subjects experienced any serious adverse events during the trial. SHAPE‐NVL and VYC‐20L showed comparable longevity and safety in mid‐face volume restoration over 2  years in Asians. Both had durable effects for up to 2  years with minimal safety concerns.